"Esquálidas criaturas de aspecto horripilante": a fome na literatura sobre a seca de 1877-79 (Ágora Journal, 2021)
The 1877-79 drought was a milestone for the literary production of Ceará, due to the moment of economic, political, and social crisis, which was going through the region that today is called the Northeast. From that period onwards, the theme of drought became predominant in many novels, constituting what is called “drought literature”. This work seeks to analyze the way in which three novelists built each one in its own way, tragic images about the hunger that affected the people of Ceará. Among these approaches, there is one, very original, which correlates hunger as the “disease of the retreatants”, and which contributed a lot to the construction of a stereotyped vision about the people of the countryside. This analysis takes place through a comparative study between the works Os Retirantes (1879) by José do Patrocínio, A Fome (1890) by Rodolfo Teófilo and Luzia-Homem (1903) by Domingos Olímpio.